IMPLEMANTASI APLIKASI BELAJAR MEMBACA JUZ'AMA BAGI ANAK USIA DINI PADA PAUD MUTIARA HATI PRINGKUMPUL - Elvia, Rosi; Puspitasari, Tuti; Maghfiroh, Annisaul (YHMM PUBLISHING, 2023)
Reading the Qur'an is a fundamental skill that should be introduced from an early age. Juz 'Amma, as the last part of the Qur'an, is often the initial stage in learning to read the Qur'an for children. However, conventional learning methods are often less interactive and less interesting for early childhood. Therefore, this study aims to develop a Juz 'Amma reading learning application specifically designed for early childhood. This application integrates multimedia elements, such as sound, animation, and digital interaction, to increase interest and effectiveness of learning. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data were collected through observation, interviews, and application trials on early childhood groups. The results of the study showed that this application can increase children's learning motivation and help them recognize and read the verses of Juz 'Amma better. This application also makes it easier for parents and teachers to accompany the learning process. Thus, the development of this Juz 'Amma reading learning application is expected to be an innovative solution in Al-Qur'an education for early childhood, as well as contributing to improving Al-Qur'an literacy from an early age.